For t 2 DNA vaccine prevents Forcipomyia taiwana (biting midge) allergy in a mouse model - Lee, M.‐F.; Song, P.‐P.; Lin, T.‐M.; Chiu, Y.‐T.; Chen, Y.‐H. (Allergy (Copenhagen), 2016)
Background Forcipomyia taiwana (biting midge) is the most prevalent allergenic biting insect in Taiwan, and 60% of the exposed subjects develop allergic reactions. Subjects with insect allergy frequently limit their outdoor activities to avoid the annoyingly intense itchy allergic reactions, leading to significant worsening of their quality of life. Allergen‐specific immunotherapy is the only known therapy that provides long‐term host immune tolerance to the allergen, but is time‐consuming and cumbersome. This study tested whether the For t 2 DNA vaccine can prevent allergic symptoms in For t 2‐sensitized mice. Materials and Methods Two consecutive shots of For t 2 DNA vaccine were given to mice with a 7‐day interval before sensitization with recombinant For t 2 proteins, using the two‐step sensitization protocol reported previously. Results The For t 2 DNA vaccine at 50 μg prevented the production of For t 2‐specific IgE (P < 0.05), as well as midge allergen‐challenge‐induced scratch bouts, midge allergen‐induced IL‐13 and IL‐4 production from splenocytes, and inflammatory cell infiltrations in the lesions 48 h after intradermal challenge. Conclusions This study is the first to demonstrate that DNA vaccine encoding midge allergen is effective in preventing allergic skin inflammation induced by biting midge. Immunotherapy using For t 2 DNA vaccine can protect mice from being sensitized by midge allergen and may be a promising treatment for biting midge allergy in the future.